PENGARUH FOTOOKSIDASI UV-C TERHADAP SIFAT FISIKOKIMIA DAN BAKING EXPANSION PATI SAGU (Metroxylon sago) - Eduard Fransisco Tethool; Angela Myrra Puspita Dewi; Abadi Jading (Agroindustrial Technology, University of Trunojoyo Madura, 2017)
Native Sago starch is difficult to used in industry because of the limitations of its phisycochemical properties. The aim of this research was to studied effect of UV-C photo-oxidation on physicochemical properties and baking expansion of sago starch. Five slurries ratio (starch : water ratio): 1:2; 1:4; 1:6; 1:8; and 1:10 were oxidized with UV-C irradiation for 20 minutes, and then compared with native sago starch. The results showed that UV-C photo-oxidation increasing amylose content and paste viscosity, but decreasing swelling power and solubility, and carbonyl and carboxyl content. Used of UV-C as a photooxidator effective to increasing baking expansion characteristic, and the best slurry ratio was 1:6, which has 6.97 ml/g specific volume or 33.7% increased from native sago starch (5.22 ml/g)